Automatyzm ludzkiej egzystencji w filmie "Dom" Jana Lenicy i Waleriana Borowczyka - Prusinowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Automatism of Human Existence in Jan Lenica's and Walerian Borowczyk's “House” The aim of this article is interpretation of the short film directed in 1958 by Jan Lenica and Walerian Borowczyk and regarded as one of the most interesting works of Polish experimental animation. Author looked upon synopsis of House as the introduction to analysis of the world portrayed in film, all its elements, symbols and their meaning. The most important question concerns condition of depersonalized human jailed in the trap of automatically repeated activities and supressing his own sexuality in his subconscious. Author also paid attention to automatism as Lenica's and Borowczyk's artistic method derived from surrealism. In this context the special usage of photography and stop motion technique of animation in House is emphasized as very important in creative process. On the basis of interpretation of the characters and objects appeared in film author drew a conclusion of the eponymous house as a metaphor of our modern world where people as the collectivity divest themselves of individual features.